A Simple Stochastic Approach to Debt Sustainability Applied to Lebanon - Gardner, E. (IMF Working Papers; Working Paper ;, 2008)
This paper applies a simple probabilistic approach to debt sustainability analysis to the case of Lebanon. The paper derives "fan charts" to depict the probability distribution of the government debt to GDP ratio under a medium-term adjustment scenario, as a result of shocks to GDP growth and interest rates. The distribution of shocks is derived from the past shocks to these variables and the related variance covariance. Because we are interested in assessing the sustainability of a particular policy scenario, we do not consider independent fiscal policy shocks or the endogenous policy response to shocks.